MORPHOMETRIC STUDIES OF ONGOLE CROSSBRED CATTLE WITH BELGIAN BLUE IN WEST JAVA - Ihsan Faturrahman; Johar Arifin; Primiani Edianingsih (Jurnal Produksi Ternak Terapan, 2022)
This study aims to determine the morphometric crosses of Belgian Blue X Cattle Ongole Crossbreeds in West Java. This research was conducted from April - July 2022. This research was conducted in West Java. The method used is descriptive exploratory. The number of samples was 18 aged 1-9 months. The data collected consists of hip height, body length, chest circumference, chest width, chest depth and shoulder height. The data obtained were analyzed using descriptive analysis. The results of the analysis can be concluded that there are uniform data on hip height, chest circumference and shoulder height at each age, body length of 3-5 months and males aged 6-9 months, a chest circumference of males aged 1-9 months, chest width of males aged 1-9 months. 6-9 months, in males at each age and not uniform in body length for males 1-2 months old and females 6-9 months old, breast circumference for females 3-5 months, chest width for males aged 1-5 months and females age 3-9 months and in the chest of females aged 3-9 months. The size discrepancy is due to the heterosis effect.